Etiology and Pathogenesis of Periodontal Disease - Dumitrescu, Alexandrina L.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
'Etiology and Pathogenesis of Periodontal Disease' represents a new concept in periodontology with its pronounced focus on understanding through knowledge rather than presenting the present valid answers. Connections between the diseases in the periodontium and general health are described in detail. Even if periodontal disease is certainly not a generally accepted cause of death, periodontal treatment may obviously save lives.
Etiology of Periodontal Disease: Dental Plaque and Calculus -- Periodontal Microbiology -- Particular Aspects of Periodontal Disease Pathogenesis -- Interrelationships Between Periodontal Disease and Mortality, Cardiovascular Disease, Metabolic Syndrome, Diabetes Mellitus -- Interrelationships Between Periodontal Disease and Adverse Pregnancy Outcomes, Respiratory Disease, Rheumatoid Arthritis, Renal Disease, Cancer, Infl ammatory Bowel Disease, Alzheimer Disease; Assessing Confounding and Effect Modification -- Genetic Variability and Periodontal Disease -- Implication of Systemic Osteoporosis on Oral Health -- Psychological Pathways in the Pathogenesis of Periodontal Disease -- Periodontal-Restorative Interactions -- Endodontic and Periodontal Interrelationship -- Occlusal Considerations in Pathogenesis of Periodontal Disease -- Orthodontics and Periodontics.
Keywords: Dentistry; Pathology; Surgery; Dentistry; Dentistry; Oral and Maxillofacial Surgery; Pathology